PEMANFAATAN DATA SATEUT PENGINDERAAN JAUH UNTUK PENENTUAN LOKASI BUDIDAYA RUMPUT LAUT DI DESA KALIUDA KEC. PAHUNGALODU, KAB. SUMBA TIMUR - NTT - KOMANG IWAN SUNIADA; B Reallino; MUJI WASIS INDRIYAWAN (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2012)
This research was canied out to support the strategic plan of the Ministry of Marine Affairs and Fisheries of Repuhlic of lndonesia that seeks to increase fisheries production through the aquaculture. Objective of this study is providing information of potential area for seaweed cultivation around Kaliuda village water territory, East Sumba, Nusa Tenggara Timur. Remote sensing data (terra or aqua MODIS satellite image), field survey data and secondary data were used for this study. Remote sensing data were used to produce Total Suspended Matter and Chlorophyll-a information, field survey data pmvided nitrate, phosphate, salinity, bottom substrate and water transparency while secondary data was used to provide bathymetry information. Geographical Information System software was used to analyze this study by using overlay technique for all parameter, which had previously been weighted and scored based on the criteria of aquatic habitat suitability. Higher score indicates that the area more suitable for marine aquaculture activities. The results showed that the potential area suitable for seaweed cultivation activities around Kaliuda village water territory, east Sumba, Nusa Tenggara Timur is about 4,79 km2 or only 24,69% from total 19,41 km• study area.